Visitors' environmental attitude and place attachment towards Kukup Island National Park, Johor, Malaysia - Razali, Nurul Rusmida (2019)
Kukup Island Johor National Park (Kukup Island JNP) as the Mangrove National Park in Malaysia, is facing of eterioration of the park’s resources where the park facilities are under critical periodical maintenance every year. This is because of the high pressures from a large group of visitors and the facilities are exposed to salt water all the time. Deterioration of the park facilities leads to the need to increase awareness about the importance of this mangrove island, which the visitors visited for education and recreational enjoyment. Therefore, the purpose of the study is to identify visitors’ attitudes toward Kukup Island JNP especially the relationship between place attachment and environmental attitude on proenvironment behavior intention towards the park. The study has been conducted on 380 respondents who visited Kukup Island JNP in March 2014 who were selected through a systematic random sampling method and the respondents answered by self-administered questionnaire.Research findings indicate that the levels of functional and emotional attachment dimensions were moderate to high respectively. The findings revealed that the park’s resources such as facilities and Kukup Island JNP’s mangrove environment increased the visitors’ attachment toward Kukup Island JNP. In addition, the level of environmental attitudes was positive on balance with nature dimension, ecological limits dimension and anthropocentrism dimension. The visitors’ awareness of consequences revealed that most of the respondents agreed there is a need for balance between human and the protection of Kukup Island JNP’mangrove environment than anthropocentric attitudes. The findings also found that there is a significant positive effect of balance with nature dimension, ecological limits dimension and place affect with pro-environment behaviour intention with total variance explained by these factors was 48.6%. The findings suggested the respondents had stronger emotional than functional attachment and proenvironmental attitude toward the park. In addition, the respondents’ viewpoint on human as a part of nature or protector of the mangrove environment at Kukup Island JNP then encourages they are to participate in pro-environment behavior intention.Therefore, the research emphasized to increase advocacy conservation efforts through place attachment and pro-environmental attitudes of park visitors. It is also suggested the park management to maintain the park resources for visitors’ satisfactory experiences toward Kukup Island JNP.